行星传动系统误差对载荷均布的影响研究 - 汤鱼; 常山; 宿吉鹏; 王志强 (Jixie chuandong)
Basing on the system errors,the kinematics equations are found for the component in the 2K—H planetary transmission system,the elasticity dynamics differential equation and dynamics model are gained.Systemic total stiffness matrix is computed and function relation between system errors and planet gear load are found.The influence is analyzed of position errors to planet gear load sharing,and the load sharing coefficients of each planet gear are calculated.